"NEW BEGINNINGS" IN SOUTH AFRICAN SHELTERS FOR THE HOMELESS: PILOTING OF A GROUP PSYCHOTHERAPY INTERVENTION FOR HIGH‐RISK MOTHER–INFANT DYADS. Issue 6 (4th September 2014) - Bain, Katherine
ABSTRACT The New Beginnings program was developed at the Anna Freud Centre and originally piloted in Her Majesty Prisons in the United Kingdom. This study aimed to explore the use of this manualized parent–infant psychotherapy group model in an African setting with high‐risk mother–infant dyads, and describes the implementation and investigation of this 12‐week group psychotherapy intervention in two Johannesburg shelters for homeless women. The measures used to investigate treatment efficacy were the Parent Development Interview (A. Slade, J.L. Aber, I. Bresgi, B. Berger, & M. Kaplan, 2004), the Emotional Availability Scales (Z. Biringen, J.L. Robinson, & R.N. Emde, 1998), the Kessler‐10 (R.C. Kessler et al., 2002), and the Griffiths Scales of Mental Development (D. Luiz et al., 2006). At pretesting, infants exhibited delays in a number of developmental areas, and mothers showed high levels of depression and generally low capacities for reflective function. While significant shifts in the mothers' capacities for reflective function were not found in the treatment condition, significant shifts were found in the infants' speech abilities and in the mothers' abilities to structure their interactions with their infants. This suggests that the program enabled mothers to become more sensitized to their infants' needs in interaction and that communication between mother and infant increased. The number of sessions attended by the dyads correlated with improvements made by the mothers and their infants.